Growth of Pontianak Siamese Shoot Culture (Citrus nobilis var. microcarpa) Supplemented with Tomato Extract and BAP (6-benzylaminopurine) - Istiani, Duwi Rida; Mukarlina, Mukarlina; Ifadatin, Siti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Pontianak Siamese (Citrus nobilis var. microcarpa) is a superior agricultural commodity especially in Sambas Regency, West Borneo. One solution to assist in the supply of Pontianak Siamese seedlings is propagation with tissue culture. This research aims to determine the impact of supplementation of tomato extract and BAP on the growth of Pontianak Siamese shoot cultures. This research was conducted from February to May 2023, at Biology Laboratory, Department of Biology, Faculty of Mathematics and Natural Sciences, Tanjungpura University. The research design used a Completely Randomized factorial design with two factors. The first factor is the treatment of BAP with concentrations 0M; 10-7M; 10-6M; and 5.10-6 M, while the second factor was tomato extract with concentrations 0% 7.5%, 10%, and 12.5%. The research results show the treatment B3T0 (5.10-6 M BAP and 0% T) has the most leaves (7 strands), the longest root length (0.30 cm), and the most roots (1 root).